DEGREES OF DAMAGE TO GANGLION CELLS OF THE RETINA AND OPTIC NERVE OF RATS UNDER THE INFLUENCE OF A MIXTURE OF ALCOHOLS - Molchanіuk, N.I. (World of Medicine and Biology, 2025)
Acute methanol poisoning causes optic neuropathy and retinal damage. The priority and extent of damage to the retinal ganglion cell and optic nerve structures in victims are discussed. We studied the ultrastructural state of these structures in rats at 1 hour 10 minutes to 3 months after a single intraperitoneal injection of an ethanol-methanol mixture (3:1 ratio; methanol dose: 0.75 g/kg body weight). Rats that received a similar injection of 100 % methanol served as controls. Ganglion cells were more resistant to the effects of a mixture of alcohols, as well as methanol, and recovered faster during the study than the structures of the optic nerve. The identified ultrastructural changes revealed the subtle mechanisms of alcohol-induced damage on eye tissues, which will help ophthalmologists more accurately treat patients affected by alcohol substitutes containing methanol, using the necessary medications.
Keywords: ultrastructure; ganglion cells; optic nerve; rats; ethanol; methanol